Kinerja Beton Polimer dengan Agregat Kasar Daur Ulang Metode Termal-Mekanik-Kimia - Kencanawati, Ni Nyoman; Ngudiyono, Ngudiyono; Biomantara, I Nyoman Hari; Mahmud, Fathmah; Merdana, I Nyoman; Hariyadi, Hariyadi (LPPM Universitas Mataram, 2025)
The use of natural coarse aggregate in large-scale concrete production can be avoided using recycled coarse aggregate as a substitute for natural aggregate. However, using recycled coarse aggregate can generally affect the quality of concrete. The excessive interfacial transition zone (ITZ) is formed due to the old mortar that is still attached, which is the weakest contact zone in recycled aggregate concrete. The addition of polymers such as Styrene Butadiene Rubber (SBR) to the recycled aggregate concrete mixture is expected to increase the strength in this area. The addition of SBR content of 0%, 2.5%, 5%, and 10% to the weight of the mixture water was carried out to review the performance of concrete in terms of its physical properties and mechanical properties. The coarse aggregate used came from recycled coarse aggregate using the Heating-Grinding-Acid Solvent (H-G-A) method. The results of the study show that H-G-A concrete with an additional SBR content of 5% exhibits superior quality compared to normal aggregate concrete. The addition of SBR shows a denser ITS area resulting in the quality of concrete increases.